Mechanistic insights into non-negligible toxicity evolution of microplastics under different aging processes - Ruixue Li; Linyong Zhi; Xiaoling Wei; Han Gong; Jun Wang (Environmental Chemistry and Ecotoxicology, 2025)
Aging processes affect the physiochemical properties, environmental behavior and ecological risk of MPs (microplastics). In this review, the toxic evolution of MPs under different aging processes and their leachate on organisms are summarized. Generally, the toxicity caused by aged MPs and leachate on organisms include growth inhibition, physiological and biochemical alterations, as well as genotoxicity. The higher toxicity of aged MPs depends on alterations in their properties including specific surface area, oxygen-containing functional groups, hydrophilicity and surface charge. Additionally, the toxicity of aged MPs was also affected by contaminants e.g., phthalocyanine blue (CuPC), biochar-derived dissolved organic matter (BDOM), fulvic acid (FA) and humic acid (HA). The release of additives, heavy metals and low molecular weight compounds during MPs aging attributes to the higher toxicity of leachate. To improve environmental relevance, the toxicity of aged MPs and their leachate should be investigated within the coexistence of diverse environmental factors and pollutants.